Great Vasyugan Mire: How the world’s largest peatland helps addressing the world’s largest problems - Kirpotin, Sergey N.; Antoshkina, Olga A.; Berezin, Alexander E.; Elshehawi, Samer; Feurdean, Angelica; Lapshina, Elena D.; Pokrovsky, Oleg S.; Peregon, Anna M.; Semenova, Natalya M.; Tanneberger, Franziska; Volkov, Igor V.; Volkova, Irina I.; et al. (Ambio, 2021)
Peatlands cover 3% of the land, occur in 169 countries, and have—by sequestering 600 Gt of carbon—cooled the global climate by 0.6 °C. After a general review about peatlands worldwide, this paper describes the importance of the Great Vasyugan Mire and presents suggestions about its protection and future research. The World’s largest peatland, the Great Vasyugan Mire in West-Siberia, forms the border between the Taiga and the Forest-Steppe biomes and harbours rare species and mire types and globally unique self-organizing patterns. Current oil and gas exploitation may arguably be largely phased out by 2050, which will pave the way for a stronger focus on the mire’s role in buffering climate change, maintaining ecosystem diversity, and providing other ecosystem services. Relevant new research lines will benefit from the extensive data sets that earlier studies have gathered for other purposes. Its globally unique character as the ‘largest life form on land’ qualifies the Great Vasyugan Mire in its entirety to be designated as a UNESCO World Heritage Site and a Ramsar Wetland of International Importance.